Aru Shah and the end of time - Chokshi, Roshani (Disney Hyperion, 2018)
Twelve-year-old Aru stretches the truth to fit in at her private school, but when she is dared to prove an ancient lamp is cursed, she inadvertently frees an ancient demon.